A concise history of Italy - Duggan, Christopher 1957-2015 (Cambridge Univ. Press, 1994)
Since its creation in 1861, Italy has struggled to develop an effective political system and a secure sense of national identity. This concise history, which covers the period from the fall of the Roman Empire in the west to the present day, looks in particular at the difficulties Italy has faced during the last two centuries in forging a nation state. The opening chapters consider the geographical and cultural obstacles to unity, and survey the long centuries of political fragmentation in the peninsula since the sixth century. It was this legacy of fragmentation which Italy's new rulers had to strive to overcome when the country became united, more by accident than design, in 1859-60. The book aims to weave together political, economic, social and cultural history, and stresses in particular the alternation between materialist and idealist programmes for forging a nation state.
Keywords: Geschichte; Italie - Histoire; Italien; Italy -- History